The Influence of Skill Competition Participation and Trainer Quality on Employee Performance: The Mediating Role of Learning Motivation in the Paper Manufacturing Industry - Andaryanto, Andaryanto; Soetjipto, Budi Eko; Winarno, Agung (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to examine the influence of participation in skill competition and trainer quality on employee performance, with learning motivation as a mediating variable. The study is grounded in the organizational phenomenon observed at PT Pabrik Kertas Tjiwi Kimia Tbk, where manpower productivity increased despite substantial workforce reduction, raising the need to explore factors that may contribute to improve performance, particularly competency development initiatives delivered through structured skill competitions. A quantitative cross-sectional design was employed, involving 226 employees who participated in a company wide skill competition within the paper manufacturing industry. The data were analysed using PLS-SEM with SmartPLS 4.1.1.4. The results demonstrate that participation in skill competition and the trainer quality have a positive and significant influence on the both motivation and employee performance. Learning motivation was also found to partially mediate the effects of both variables on performance. This motivation was also found to partially mediate the effect of both variables on performance. These findings indicate that competition based learning activities and high quality instructional facilitation are essential drivers of intrinsic motivation and performance improvement. Moreover, the result strengthen the relevance of Self-Determination Theory (SDT), Transfer of Training theory, and provide empirical support for the Resource-Based View (RBV) within industrial settings. Future research opportunities include exploring long term dynamics and broader organizational factors that may further shape these relationships.